1992
DOI: 10.1128/aem.58.1.229-232.1992
|View full text |Cite
|
Sign up to set email alerts
|

Sheared-Root Inocula of Vesicular-Arbuscular Mycorrhizal Fungi

Abstract: For efficient handling, vesicular-arbuscular mycorrhizal fungi should be processed into small and uniform inocula; however, processing can reduce the inoculum density. In this article we describe the preparation and use of sheared-root inocula of Glomus spp. in which inoculum densities were increased during processing. Our objectives were to determine inoculum viability and density after shearing and to ascertain if the sheared inocula could be pelletized or used with a gel carrier. Roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…Cryopreservation of fungal spores using porous beads was also achieved by Chandler (1994), and ectomycorrhizal fungi entrapped in alginate gels have been shown to retain their infectivity after storage at 4mC for several months (Mauperin et al, 1987). Similar results were reported for AM fungi by Strullu & Plenchette (1991) and Sylvia & Jarstfer (1992). Declerck et al (1996b) further demonstrated that entrapped, monoxenically produced spores of G. versiforme were able to re-infect plants grown in vivo.…”
Section: supporting
confidence: 82%
“…Cryopreservation of fungal spores using porous beads was also achieved by Chandler (1994), and ectomycorrhizal fungi entrapped in alginate gels have been shown to retain their infectivity after storage at 4mC for several months (Mauperin et al, 1987). Similar results were reported for AM fungi by Strullu & Plenchette (1991) and Sylvia & Jarstfer (1992). Declerck et al (1996b) further demonstrated that entrapped, monoxenically produced spores of G. versiforme were able to re-infect plants grown in vivo.…”
Section: supporting
confidence: 82%
“…It provides an excellent chance for plant researchers to deeply study the behavior of plant root under different conditions and without any complications. Until now, many researchers had conducted plant root research and experimental studies root response to drought [64], effects of different oxygen concentrations on plant root development [65,66], root microorganism [67][68][69], arbuscular mycorrhizal fungi production [70], and legume-rhizobia interaction [71]. Furthermore, studies also practiced the technique by growing vegetables, fruits, herbs, and medicinal root-based plant [72][73][74] such as tomato, potato, soybean, maize, lettuce, Anthurium andreanum, and Acacia mangium [15,59,[75][76][77][78][79].…”
Section: The Aeroponic Systemmentioning
confidence: 99%
“…Few companies offer AM fungi inocula for agricultural and horticultural uses. Endomycorrhizal inocula are available in the form of spores (propagules formed outside the root) and root pieces containing vesicles (propagules formed inside the root tissue) (Sylvia and Jarstfer, 1992). They are added directly into the surrounding soil of seeds and plantlets.…”
Section: Introductionmentioning
confidence: 99%